Impact of the COVID-19 pandemic on malaria cases in health facilities in northern Ghana: a retrospective analysis of routine surveillance data - Heuschen, Anna-Katharina; Abdul-Mumin, Alhassan; Adokiya, Martin Nyaaba; Lu, Guangyu; Jahn, Albrecht; Razum, Oliver; Winkler, Volker; Müller, Olaf (Malaria journal, 2022)
The COVID-19 pandemic and its collateral damage severely impact health systems globally and risk to worsen the malaria situation in endemic countries. Malaria is a leading cause of morbidity and mortality in Ghana. This study aims to describe the potential effects of the COVID-19 pandemic on malaria cases observed in health facilities in the Northern Region of Ghana.